A Serious Games System for the Analysis and the Development of Visual Skills in Children with CVI: A Pilot Study with Kindergarten Children - Gaggi, Ombretta; Sgaramella, Teresa Maria; Nota, Laura; Bortoluzzi, Margherita; Santilli, Sara (Smart Objects and Technologies for Social Good, 2017)
The development of visual skills is crucial in sustaining an adaptive cognitive and social development in children. The paper describes the result of a pilot study, involving a group of 4 years old children, with a set of serious games to improve the assessment and rehabilitation process in children with CVI. The system uses an eye tracker system to correctly measure the performances of the child and his/her capability to watch and touch a moving object at the same time and to perform ab cognitive visual decision making.